The 4 Cs - Alshammari, Ayed (My University, 2019)
The research investigated the core problem of the Saudi education system that the system for 1-12 still relies on the 3 Rs, which are arithmetical, writing, and reading skills. As a result, the 3 Rs are not enough to provide students with their needs and life experiences for the 21st century. One of the most crucial drawbacks is not using technology. I believe that the major problem in Saudi system is not using the 21st century skills which are creativity, collaboration, critical thinking, and communication. These skills are important to encounter all changes and challenges these days. These skills are needed and must be embedded within the curricula in order to motivate students and let them make the most of their knowledge in a creative way. Also, they let the students use their high skills. I would apply a series of workshops in the Rafha district schools that provide teachers with these skills and how to enact them inside the classroom. Therefore, the solution that surfaced when addressing this issue is to teach these concepts and train teachers and students how to enact them through lessons.